Adolescent Mental Health 2015
DOI: 10.1201/b18222-16
|View full text |Cite
|
Sign up to set email alerts
|

- Cyber and Traditional Bullying Victimization as a Risk Factor for Mental Health Problems and Suicidal Ideation in Adolescents

Abstract: Background: This systematic review provides a narrative synthesis of the evidence on the effectiveness of mental health promotion interventions for young people in low and middle-income countries (LMICs). Commissioned by the WHO, a review of the evidence for mental health promotion interventions across the lifespan from early years to adulthood was conducted. This paper reports on the findings for interventions promoting the positive mental health of young people (aged 6-18 years) in school and community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 17 publications
3
35
0
3
Order By: Relevance
“…Hence these hidden forms of human capital could potentially serve as novel but critical targets in programs designed to boost the education and labor market outcomes of women. Importantly, an increasing evidence base shows the potential of interventions to increase youth self-efficacy and mental health in India as well as other countries (Barry et al, 2013;Krishnan & Krutikova, 2013;Leventhal et al, 2015). In Jharkhand, our analyses show that modifiable factors with strong correlations to self-efficacy include social supports, participation in training programs, and exposure to successful women.…”
Section: C Discussion Of Findingsmentioning
confidence: 82%
“…Hence these hidden forms of human capital could potentially serve as novel but critical targets in programs designed to boost the education and labor market outcomes of women. Importantly, an increasing evidence base shows the potential of interventions to increase youth self-efficacy and mental health in India as well as other countries (Barry et al, 2013;Krishnan & Krutikova, 2013;Leventhal et al, 2015). In Jharkhand, our analyses show that modifiable factors with strong correlations to self-efficacy include social supports, participation in training programs, and exposure to successful women.…”
Section: C Discussion Of Findingsmentioning
confidence: 82%
“…improved self-esteem, motivation and selfefficacy, increased pro-social bonding, cognitive, social and emotional competence, increased personal and social skills, higher levels of youth civic engagement, higher levels of behavioral and emotional engagement with school, and improved academic performance and so on. 34,35 A bulk of the studies have focused on youth at risk and utilized content targeting education about the specific kinds of risk in question (substance use, sexual and reproductive health, youth from slums or poverty ridden areas, etc. ), though there are a few that have focused on general samples of youth.…”
Section: Pyd Based Youth Mental Health Promotionmentioning
confidence: 99%
“…However, 96 percent of the young people sampled 'looked forward' to participating in the sports and play activities because they were 'very important' to them, compared with just over half (54 percent) of young people who were not in agreement with the statement: 'The main thing is to have fun' (p. 1,151). The author concluded that possibly, given young people's current circumstances, 'being able to engage in sport and play has a more serious importance than "just" doing it for enjoyment'.…”
Section: Ensuring Providers Are Sufficiently Trained To Deliver Progrmentioning
confidence: 92%